(untitled) (JURNAL ENFIT : Entomologi dan Fitopatologi, 2023)
Potato (Solanum tuberosum L.) is one type of horticultural crop with high economic value. One of the diseases of potato plants is bacterial wilt. Bacterial wilt is caused by the bacterium Ralstonia solanacearum. This study aims to determine the incidence of bacterial wilt disease on potato plants in Insil Village, Bolaang Mongondow Regency, which was carried out from August to October 2021, located in Insil Village, Bolaang Mongondow Regency and at the Plant Pests and Diseases Laboratory, Faculty of Agriculture, Sam Ratulangi University. The research was conducted using a survey method with purposive sampling observations. Observations were made on potato plants four weeks after planting. The research was conducted in three different planting locations. Each location measured 30 m x 30 m. In each location, plots were made with diagonal lines measuring 3 m x 3 m and 36 plants were taken from each plot. Plots were made to determine the symptoms of attack caused by R. solanacearum bacteria. The results showed that the highest incidence occurred in location C at 24.44%, followed by location B at 16.66% and the lowest incidence occurred in location A at 16.10%. The average incidence of bacterial wilt disease in potato plants in Insil Village, Bolaang Mongondow Regency is in location A with an average of 8.88%, location B with an average of 7.49% and location C with an average of 14.71%. Further research is needed to determine the factors that influence the development of wilt incidence in potato plants in Insil Village, Bolaang Mongondow Regency.